Do consultation charges deter general practitioner use among older people? A natural experiment - Richard Layte; Hannah McGee; Ann O'Hanlon (The Economic and Social Research Institute (ESRI), 2007)
Background: A change in the pricing of general practitioner care in the Republic of Ireland in 2001 provides a natural experiment of the influence of economic incentives on GP visiting. Methods: Social surveys (N=937 in 2000 & N=1053 in 2004) were carried out before and after the change in pricing arrangements. OLS and logistic regression were used to examine change in both the overall probability of attending the GP and the frequency of visiting in the previous year. Results: 93% in 2000 and 95% in 2004 visited their GP at least once. Where the proportion of those aged 65 to 69 visiting at least once fell by 1% between 2000 and 2004, the proportion aged 70 to 74 increased by 4.6%; those 75 to 79 increased by 6.3%; those aged 80 to 84 increased by 3.2%. Frequency of visiting remained stable at 5.3 visits per year but increased with age and worse health. Logistic regression models confirmed the increase in the probability of visiting for over 70s between 2000 and 2004.
Keywords: 330; General practice; utilisation; equity; Gesundheitsversorgung; Alte Menschen; Methode der kleinsten Quadrate; Schätzung; Irland